2022
DOI: 10.3390/ijerph19031686
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Influential Users in the Promotion and Marketing of Heated Tobacco Products on Instagram: A Social Network Analysis

Abstract: While an increasing body of the literature has documented the exposure to emerging tobacco products including heated tobacco products (HTPs) on social media, few studies have investigated the various stakeholders involved in the generation of promotional tobacco content. This study constructed a social network of Instagram users who posted IQOS content, a leading HTP brand, between 1 January and 5 April 2021 and identified users who positioned near the center of the network. We identified 4526 unique Instagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Prior social media studies have looked at influencer marketing of HTPs and user-generated content of HTPs. For example, one prior study of IQOS on Instagram found that there were over 4000 accounts that used #IQOS in their account description and that 27 of these accounts had over 50 000 followers 4. As the current study identified three PMI IQOS Instagram accounts with over 50 000 followers, the current study expands prior work by identifying PMI-sponsored official accounts and by showing that at least for Instagram, PMI accounts are a small but significant part of the total Instagram IQOS ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior social media studies have looked at influencer marketing of HTPs and user-generated content of HTPs. For example, one prior study of IQOS on Instagram found that there were over 4000 accounts that used #IQOS in their account description and that 27 of these accounts had over 50 000 followers 4. As the current study identified three PMI IQOS Instagram accounts with over 50 000 followers, the current study expands prior work by identifying PMI-sponsored official accounts and by showing that at least for Instagram, PMI accounts are a small but significant part of the total Instagram IQOS ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of the literature has documented that social media marketing of novel tobacco products including e-cigarettes, hookah and cigars exists and is effective 3–7. Many e-cigarettes, hookah and cigar products have official social media product pages and accounts 3 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media platforms such as Instagram are now a common platform for the public to share their opinions and are widely used for studying HTPs like IQOS [13,14]. About 71% of the young adults aged between 18 and 29 claimed that they have been Instagram users, which overlaps with the demographic group that IQOS potentially attracts and actual IQOS users [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…About 71% of the young adults aged between 18 and 29 claimed that they have been Instagram users, which overlaps with the demographic group that IQOS potentially attracts and actual IQOS users [15][16][17][18]. A recent investigation on IQOS marketing showed that IQOS has been widely promoted and marketed on Instagram through influential users [14]. One previous study focusing on characterizing the vaping-related content on Instagram through descriptive analyses has yielded informative outcomes, and the success of this vaping-related study indicates that the descriptive analysis on Instagram is a practical method to gain insights into how tobacco products are discussed or even marketed on social media [19].…”
Section: Introductionmentioning
confidence: 99%